2021
DOI: 10.3389/fimmu.2021.683249
|View full text |Cite
|
Sign up to set email alerts
|

Total Glucosides of Paeony Ameliorate Pristane-Induced Lupus Nephritis by Inducing PD-1 ligands+ Macrophages via Activating IL-4/STAT6/PD-L2 Signaling

Abstract: Macrophages, a major subset of innate immune cells, are main infiltrating cells in the kidney in lupus nephritis. Macrophages with different phenotypes exert diverse or even opposite effects on the development of lupus nephritis. Substantial evidence has shown that macrophage M2 polarization is beneficial to individuals with chronic kidney disease. Further, it has been reported that PD-1 ligands (PD-Ls) contribute to M2 polarization of macrophages and their immunosuppressive effects. Total glucosides of paeony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Therefore, repairing the dynamic balance between Th1/Th2/Th17/Treg cells is crucial for treating SLE and OP. 29,30 (Mechanism of action of IL-4 in SLE and OP is shown in Figure 10)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, repairing the dynamic balance between Th1/Th2/Th17/Treg cells is crucial for treating SLE and OP. 29,30 (Mechanism of action of IL-4 in SLE and OP is shown in Figure 10)…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, repairing the dynamic balance between Th1/Th2/Th17/Treg cells is crucial for treating SLE and OP. 29,30 (Mechanism of action of IL-4 in SLE and OP is shown in Figure 10)
Figure 9.Mechanism of action between CD4 + Th and Th1/Th2/Th17/Treg cells.
Figure 10.Mechanism of action of IL-4 in SLE and OP.
…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, IRF1 is the key factor of PD-L1 promoter function, while PD-L2 is mainly regulated by STAT1/3 [ 33 ], which also explain our results that only PD-L2 is upregulated in LXN −/− macrophages. It has been reported that PD-1 ligands (PD-Ls) contribute to the M2 polarization and immunosuppressive effects of macrophages [ 48 ], and PD-L2 expression correlated with other established markers for alternatively activated macrophages [ 49 ]. As early as ten years ago, Huber et al reported that PD-L2 appears to be a more specific and distinctive marker for M2, and IL-4 induced the expression of PD-L2 on classically activated macrophages, however, LPS increased the expression of PD-L1 on M2 [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…OVA can be used to induce the AR model 20 and was used to treat sorted macrophages from healthy controls for 0, 6, 12, 24, or 48 h at a concentration of 5 mg/ml 21 . In some cases, macrophage M2 polarization was induced by IL‐4 at a concentration of 20 ng/ml 22 …”
Section: Methodsmentioning
confidence: 99%